Nopalea cactus pear fertilized with nitrogen: morphometric, productive and nutritional characteristics (Acta Scientiarum. Animal Sciences, 2018)
This study aimed to evaluate the structural, productive and nutritional characteristics of cactus pear (Nopalea cochenillifera Salm Dyck. cv. Miúda/Doce) under five nitrogen doses and two planting orientations. A randomized block design in a 5 x 2 factorial scheme was used in the scheme: five nitrogen doses (0, 150, 300, 450 and 600 kg of N ha-1), and two planting orientations (North/South and East/West), with three replicates. Except for the thickness of the secondary (p = 0.04) and tertiary cladodes (p = 0.02), the morphometric characteristics of the cactus pear were not influenced by the nitrogen doses (p > 0.05). The mean height was 120 cm, the areas of the primary, secondary and tertiary cladodium were 160.9; 208 and 158.4 cm², respectively. The application of nitrogen fertilizer, in the dry conditions and doses evaluated, did not affect the production of green matter (PGM, p = 0.56), dry matter (PDM, p = 0.74) and dry matter content (DM, p = 0.72), with averages of 276 t ha-1, 43.2 t ha-1 and 15.7%, respectively. The increase of the nitrogen doses does not improve the majority of the morphometric characteristics or the dry matter yield of the cactus pear cv. Miúda at 730 days after planting.